Columella necrosis in a child secondary to nasal continuous positive airway pressure during neonatal period - Priyanka, Menon; Mohd Nor, Khadijah; Kulasegarah, Jeyanthi (Malaysian Medical Association, 2021)
The advent of continuous positive airway pressure ventilation as a mode of treatment for respiratory distress syndrome for premature infants has increased the risk of nasal injuries such as pressure necrosis. We describe a case of a 24-week infant who received CPAP ventilation as a mode of ventilatory support for respiratory distress syndrome and the complication of pressure necrosis of the columella. There are many factors that predispose an infant receiving CPAP ventilation to nasal injury. Many strategies can be employed to reduce the incidence of nasal injuries such as the use of nasal barrier dressings, the use of nasal high flow oxygen (nHF) cannula instead of CPAP ventilation, and the use of nasal masks instead of nasal prongs for CPAP ventilation delivery. The treatment of pressure necrosis can be either medical or surgical. The use of ointments or growth sprays can be used in cases of skin breakdown. Surgical reconstruction can be offered in cases of nasal deformity.